Comparison of the diagnostic value of four scoring systems in primary sjögren’s syndrome patients - Qi, Xuan; Sun, Chao; Tian, Yu; Han, Yuxiang; Peng, Chenxing; Jin, Hongtao; Gao, Lixia; Guo, Huifang (Immunology letters, 2017)
•The mean scores of pSS patients were significantly higher than controls.•The AUC of 0–16 SGUS is significantly higher than Submandibular salivary glands scoring system.•No significant difference was observed in the sensibility and specificity of the four scoring systems. We attempted to evaluate the diagnostic value of different salivary gland ultrasonography (SGUS) scoring systems for primary sjögren’s syndrome (pSS). Total 134 patients with pSS and 109 non-SS sicca controls were included in our study. All the cases were evaluated by four scoring systems (such as 0–16 SGUS, 0–3 SGUS, Parotid glands and Submandibular salivary glands scoring system). The receiver operating characteristic (ROC) analysis was performed for the four scoring systems. The mean scores of pSS patients were significantly higher than that of controls by four scoring systems (P<0.01). The AUC (area under the curve) of (0–16) SGUS scoring system (0.916) was higher than Submandibular salivary glands scoring system (0.885) (P=0.016). No significant difference of AUC was observed in (0–3) SGUS scoring system, compared with 0–16, parotid gland and submandibular salivary glands scoring system. The optimal cutoff value of (0–16) SGUS, (0–3) SGUS, Parotid gland, Submandibular salivary glands scoring system was 5, 2, 3, 2, respectively. There was no significant difference in the sensitivity and specificity of the four scoring systems. The simplified parotid gland scoring system may be the simplified and feasible method for pSS diagnosis.